A Pilot Study of Symptoms of Major Depressive Disorder in Medical Students at an Osteopathic Medical School Before and After High-Stakes Examinations - Arabatzis TJ; Doroshenko J; Ashraf MA; Smith RM (Advances in Medical Education and Practice, 2023)
Taxiarhia J Arabatzis,1 Justin Doroshenko,2 Muhammad A Ashraf,3 Ryan M Smith4 1Department of Internal Medicine-Pediatrics Residency Program, Geisinger Medical Center, Danville, PA, USA; 2Department of Emergency Medicine Residency Program, University of Texas Health San Antonio, San Antonio, TX, USA; 3Diagnostic Radiology Residency Program, Hartford Hospital, Hartford, CT, USA; 4Department of Psychiatry, University of New England College of Osteopathic Medicine, Biddeford, ME, USACorrespondence: Ryan M Smith, Email rsmith8@une.eduBackground: Given the high prevalence of symptoms of major depressive disorder (MDD) in medical students, identifying factors that impact the development of such symptoms is important. Previous data suggest that medical students can experience symptoms of MDD after medical school exams. It is not known if medical students experience more symptoms of MDD directly before or after exams. The aim of the current study is to determine the prevalence of symptoms of MDD in first- and second-year medical students directly before and after high-stakes medical school examinations.Methods: Two anonymous surveys were sent via REDCap to first- and second-year medical students at the University of New England College of Osteopathic Medicine. A pre-exam survey on the day of the exam asking about the past three days’ MDD symptoms, and a post-exam survey sent three days after the exam asking about MDD symptoms experienced after the exam was sent out to a total of 391 students with a response rate of 23%.Results: First- and second-year medical students regardless of gender experienced symptoms of MDD at higher rates before exams than afterwards. Female students experienced symptoms of MDD (as defined by the DSM-5) including sadness, sleep disturbances, and feelings of guilt or worthlessness at a greater rate compared to males before exams. After exams, females were more likely to experience sleep disturbances and decreased energy. Second-year male students were the least likely to experience symptoms of MDD.Conclusion: First- and second-year medical students can experience symptoms of MDD surrounding exams. This study highlights the emotional burden that students may carry near exams. It underscores the importance of further research on this topic to evaluate the effect exams have on the mental health of medical students during their training.Keywords: depression, medical school, examinations, gender, MDD